PENGARUH BRAND IMAGE DAN AWARENESS MELALUI MARKETING MIX TERHADAP KEPUTUSAN PEMBELIAN MOMOYO ICE CREAM DAN FRUITY MUARA TEWEH - Tania Jannah; Lita Amelliya Putri (JURNAL ILMU EKONOMI (MANAJEMEN PERUSAHAAN) DAN BISNIS, 2025)
The purpose of this study was to examine whether there is an influence between brand image and brand awareness through the marketing mix on purchasing decisions of Momoyo Ice Cream and Fruity in Muara Teweh. This study involved consumers of Momoyo Ice Cream & Fruit Tea in Muara Teweh with a population of 100 people, who were also sampled using stratified random sampling techniques. Data were obtained through questionnaires and literature studies as research instruments. Data analysis was carried out using SPSS 27.0 For Windows. The results showed that brand awareness had a partial significant effect on the marketing mix, while brand image and brand awareness were proven to have a simultaneous significant effect. From the Standardized Coefficients Beta test, the most influential variable on purchasing decisions was brand awareness (X2) compared to brand image and marketing mix.